2013
DOI: 10.1038/ncb2848
|View full text |Cite
|
Sign up to set email alerts
|

PtdIns(3)P-bound UVRAG coordinates Golgi–ER retrograde and Atg9 transport by differential interactions with the ER tether and the beclin 1 complex

Abstract: ER-Golgi membrane transport and autophagy are intersecting trafficking pathways that are tightly regulated and crucial for homeostasis, development and diseases. Here, we identify UVRAG, a Beclin1-binding autophagic factor, as a PI(3)P-binding protein that depends on PI(3)P for its ER localization. We further show that UVRAG interacts with RINT-1, and acts as an integral component of the RINT-1-containing ER tethering complex, which couples phosphoinositide metabolism to COPI-vesicle tethering. Displacement or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 59 publications
5
95
0
Order By: Relevance
“…Several studies demonstrated that RINT1 is involved in ER-Golgi trafficking in vitro. 16,17,[19][20][21] Lin et al 19 associated the observed mitotic defects with Golgi dispersion and centrosome amplification. We demonstrated that centrosome amplification in MEFs is not correlated with mitotic defects and in NSC is not detected at all.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies demonstrated that RINT1 is involved in ER-Golgi trafficking in vitro. 16,17,[19][20][21] Lin et al 19 associated the observed mitotic defects with Golgi dispersion and centrosome amplification. We demonstrated that centrosome amplification in MEFs is not correlated with mitotic defects and in NSC is not detected at all.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that ER stress led to autophagy [30][31][32] and that RINT1 was associated with autophagy. 21 Therefore, we decided to monitor autophagy in Rint1-deficient cortices. We found that Rint1-deficient neurons exhibited autophagosome accumulation as indicated by the accumulation of LC3B punctate in cortical neurons and the increased conversion of the unconjugated LC3B-I to the phosphatidylethanolamine-conjugated form LC3B-II in E15.5 and E17.5 cortices (Figures 6a and b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…155 Interestingly, UVRAG, as a PtdIns3P-binding effector per se, shuttles between ER and autophagic membranes, coordinating different membrane trafficking events, and maintaining organelle homeostasis under various conditions. 156 In a PtdIns3P-dependent manner, UVRAG is bound to the ER tethering protein complex RINT1-ZW10-NBAS, involved in Golgi-to-ER transport; however, when autophagy is induced, UVRAG is dissociated from the ER and is bound to the SH3GLB1/Bif-1-BECN1-PIK3C3 complex. 156 UVRAG is necessary for vesicle tethering and fusion in the endocytic system.…”
Section: Regulation Of Autophagy By Pik3c3 Via Atg14mentioning
confidence: 99%